Studi Kepustakaan Penerapan Solution-Focused Brief Therapy (SFBT) dalam Bimbingan dan Konseling - Nirmala, Yudith Trisna; Susilo, Agus Tri; Suryawati, Citra Tectona (Universitas Sebelas Maret, 2023)
The purpose of this research is to examine the application of SFBT which includes the objectives, scope, procedures, and the success of its application in guidance and counseling. The research method used is literature review. The data source used is how many 20 research journals that show a connection with the problem to be studied. The data collection technique used is documentation. The data analysis technique used is content analysis. The results of this study are: (1) The target of application of SFBT is school age students who are classified as children and adolescents, (2) Scope of application of SFBT the environmental space is in the form of personal, social emotional, behavioral, and academic problems, (3) The methods / techniques for applying SFBT include exceptional questions, miracle questions, scaling questions (4) The procedure for implementing SFBT consists of 3 main stages, (5) The successful implementation of SFBT, namely is effectively capable and successful in reducing aggressive behavior, increasing perceptions of social competence, self-perception, sense of coherence, self-esteem, self-efficacy, self-regulation, reducing symptoms of depression, overcoming burnout, self-concept, managing academic stress, overcoming addiction internet, self-adjustment, understanding the problems faced, helping in understanding student needs, controlling compulsive internet use, decreasing academic procrastination behavior.